Дитинство у контексті історії - Якубовська-Кравчик, К. (Слово і Час, 2020)
У статті проаналізовано проблему вписування дитинства в історію
світу на прикладі романів С. Жадана «Інтернат» і B. Рафєєнка «Довгі часи». Контекстом слугують спогади учасників Революції Гідності,
зафіксовані в книжці Н. Гук «Звичайні герої», й записки про війну, що
ввійшли в книжку А. Чеха «Точка нуль». Розглянуто питання про роль
дитинства: ідеться про складник внутрішньої метанарації як необхідний для героя світоглядний орієнтир; про накопичення різного досвіду й
знань, що формують спосіб сприйняття світу; порушено проблематику
наративу розпаду радянської імперії, часу трансформації та війни. The paper focuses on the problem of a childhood immersed in history based on Serhiy
Zhadan’s “Boarding School” (“Internat”) and V. Rafeienko’s “Long Days” (“Dovhi dni”),
with references to the memories of those who took part in the revolution of dignity collected
by Natalia Huk. In traditional literary texts, the image of childhood was typically
utopian. In the analyzed works, the presented world of a child is often not perfect. We rather
deal with the category of exile from paradise, and often from the area of child naivety. The
young protagonist is forced to confront an alien, brutal world. According to Foucault, “history
is a discourse of power”. In these works, the political games and temptation to dominate
the world are the phenomena that cause consequences having an impact on the youngest
ones. So what is childhood like in the texts covering war and revolution? The authors use
child memories as a kind of background against which they can show the present day of
their protagonists. It may be an important point of reference, something that accompanies
the person until the old age. Childhood narratives are the element that writers use for constructing
images of the future, they are a component of internal metanarration guiding the
protagonists in the world.
In retrospect, the characters begin to perceive childhood as accumulated experiences
of various interaction types, the knowledge that even years later shapes their perception of
the world. Besides, it brings them closer to the people with whom some kind of memories
may be shared. It creates a community. The experience of childhood is shaped by a narrative
common to the group regarding it as a norm.
In opposition to the official history, the authors put the protagonists’ memory first,
which is a kind of compass helping them to orient themselves in the ever-changing and not
always understandable reality.